Variability in interhospital trauma data coding and scoring: A challenge to the accuracy of aggregated trauma registries. Issue 3 (September 2015) - Arabian, Sandra S.; Marcus, Michael; Captain, Kevin; Pomphrey, Michelle; Breeze, Janis; Wolfe, Jennefer; Bugaev, Nikolay; Rabinovici, Reuven
Abstract : BACKGROUND: Analyses of data aggregated in state and national trauma registries provide the platform for clinical, research, development, and quality improvement efforts in trauma systems. However, the interhospital variability and accuracy in data abstraction and coding have not yet been directly evaluated. METHODS: This multi-institutional, Web-based, anonymous study examines interhospital variability and accuracy in data coding and scoring by registrars. Eighty-two American College of Surgeons (ACS)/state-verified Level I and II trauma centers were invited to determine different data elements including diagnostic, procedure, and Abbreviated Injury Scale (AIS) coding as well as selected National Trauma Data Bank definitions for the same fictitious case. Variability and accuracy in data entries were assessed by the maximal percent agreement among the registrars for the tested data elements, and 95% confidence intervals were computed to compare this level of agreement to the ideal value of 100%. Variability and accuracy in all elements were compared (χ 2 testing) based on Trauma Quality Improvement Program (TQIP) membership, level of trauma center, ACS verification, and registrar's certifications. RESULTS: Fifty registrars (61%) completed the survey. The overall accuracy for all tested elements was 64%. Variability was noted in all examined parameters except for the place of occurrence code in all groups and the lower extremity AIS code in Level II trauma centers and in the Certified Specialist in Trauma Registry– and Certified Abbreviated Injury Scale Specialist–certified registrar groups. No differences in variability were noted when groups were compared based on TQIP membership, level of center, ACS verification, and registrar's certifications, except for prehospital Glasgow Coma Scale (GCS), where TQIP respondents agreed more than non-TQIP centers ( p = 0.004). CONCLUSION: There is variability and inaccuracy in interhospital data coding and scoring of injury information. This finding casts doubt on the validity of registry data used in all aspects of trauma care and injury surveillance.